Common weeds of East Africa - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1988)
Terry, P J and R W Michieka, 1987. Common Weeds of East Africa FAO, Rome, 184 pp ISBN 92-5-002426-6 FAO code 14 AGRIS H60 1987